A Study on Strength Characteristics of Concrete by Addition of Basalt Fiber (International Journal of Innovative Research in Computer Science & Technology, 2022)
Concrete is one of the oldest and most  widely used building materials in the world, mostly because  it is inexpensive and readily available. In all areas of  contemporary construction, concrete has become a key  component of structures. It is challenging to name another  building material that is as versatile as concrete. When  strength, durability, impermeability, fire resistance, and  absorption resistance are needed, concrete is the ideal  material to use. This study's main goal is to compare plain  M30 grade concrete to basalt fiber concrete in terms of  compressive, flexural, and splitting tensile strength. Basalt  fiber is a substance created from the incredibly tiny basalt  fibers that naturally occur in volcanic rocks that are the  result of frozen lava. In the aerospace and automobile  industries, it is utilized as a fire-resistant textile. Fibers are  typically added to concrete to strengthen its structural  stability. Due to its remarkable qualities, such as resistance  to corrosion and low thermal conductivity, basalt fiber is  currently among the fibers that is gaining more prominence.  Additionally, it increases the concrete's toughness, flexural  strength, and tensile strength. Important concrete  constructions like nuclear power stations, roads, and bridges  can employ it to prolong their lifespan. The variable factors  taken into account in this study were M30 grade concrete  cubes, cylinders, and beams, which were cast and cured in  portable water for 28 days. The cubes' dimensions were 150  x 150 x 150 mm, the cylinders' dimensions were 150 mm  (dia) x 300 mm (depth), and the beams' dimensions were  500 x 100 x 100 mm. Then, at 7, 14, and 28 days, the  specimens were examined for split tensile strength, flexural  strength, and compression strength using ordinary concrete  with and without basalt fiber.
Keywords: Split tensile strength; Flexural strength; Compressive strength; Basalt fiber; and Concrete